Beyond The Good Earth : Transnational Perspectives on Pearl S. Buck - Cole, John J. K.; Haddad, John Rogers (Book collections on Project MUSE., 2019)
"How well do we really know Pearl S. Buck? Many think of Buck solely as the Nobel laureate and Pulitzer Prize-winning author of The Good Earth, the novel that explained China to Americans in the 1930s. But Buck was more than a novelist and interpreter of China. As the essays in Beyond The Good Earth show, she possessed other passions and projects, some of which are just now coming into focus. Who knew, for example, that Buck imagined and helped define multiculturalism long before it became a widely known concept? Or that she founded an adoption agency to locate homes for biracial children from Asia? Indeed, few are aware that she advocated successfully for a genocide convention after World War II and was ahead of her time in envisioning a place for human rights in American foreign policy. Buck's literature, often dismissed as simple portrayals of Chinese life, carried a surprising degree of innovation as she experimented with the styles and strategies of Modernist artists. In Beyond The Good Earth, scholars and writers from the United States and China explore these and other often overlooked topics from the life of Pearl S. Buck, positioning her career in the context of recent scholarship on transnational humanitarian activism, women's rights, and civil rights activism"--